A systematic literature review: Self-efficacy toward mathematical reasoning ability - Narpila, Suci Dahlya; Tarwiyah; Purba, Oktaviana Nirmala; Purba, Azrina; Lestari, Indah (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
This study is a systematic literature review aimed at describing various research findings related to students’ mathematical reasoning ability in relation to their self-efficacy levels. The method used is a systematic literature review by applying the keywords self-efficacy and reasoning ability, along with predefined inclusion criteria to select relevant articles. Articles that met the inclusion criteria were then analyzed qualitatively to draw valid and accountable conclusions. The results of the analysis reveal inconsistencies across studies regarding the influence of self-efficacy on students’ mathematical reasoning ability. Differences were also found in how varying levels of self-efficacy affect students’ performance in solving mathematical reasoning tasks. These discrepancies may stem from several factors, including sample limitations, differences in methodological approaches, the theoretical frameworks adopted, and variations in contextual field conditions. Therefore, further research is needed that involves more diverse variables and employs more comprehensive methodological designs to gain a more consistent and holistic understanding of the relationship between self-efficacy and students’ mathematical reasoning ability.